Effect of the self-cleaning coating surface in the temperature and soiling losses of photovoltaic modules. - Cañete-Torralvo, Cristina; Moreno-Sáez, Rafael Jesús; Piliougine Rocha, Michel; Sidrach-de-Cardona-Ortin, Mariano; Carretero-Rubio, Jesús Eduardo; Hirose, Jun-ichi; Ogawa, Shuichiro (WIP Munich, 2012)
Soiling on photovoltaic modules has a straight effect on the transmittance and hence significant energy losses. The economic cost due to these losses can be important in the case of large-scale plants, especially for those located in dry areas. Asahi Kasei Corporation has designed and developed a new coating for photovoltaic modules with self-cleaning and anti-reflectiveness properties. The deposition of such coating on the surface of the modules has a positive effect on their global performance. The objective of this paper is to evaluate this coating by comparing the energy produced by several modules of the same model, some of them with anti-soiling coating and other without it. Obtained results quantify the relationship between soiling and energy losses. During long periods without rain, these losses grow up gradually until first rainfalls. Modules with the coating have experimented mean daily energy losses around 2.7%, whereas in the case of the modules without the coating this value reaches 3.6%.
Keywords: Energía fotovoltaica; Anti-soiling coating; Energy rating; Optical losses